Using IPFS for Automatic Digital Intellectual Property Registration in Web3 Platforms - Yusuf Tojiri; Maulana Arif Komara; Alfri Adiwijaya; Nasrul Hidayat; Cristiano Gatot Wagner; Marviola Hardini (Pandawan, 2026)
This study proposes an IPFS-based system for automatic digital intellectual property registration within Web3 platform environments. The rapid development of digital technology has encouraged the transformation of Intellectual Property Rights (IPR) protection from manual systems to more secure and efficient digital mechanisms. However, current IPR registration processes remain centralized, slow, and vulnerable to data tampering. Based on this issue, this study aims to design and test an automatic IPR registration system using the InterPlanetary File System (IPFS) as a decentralized storage solution. This research employs a software engineering method with a prototyping approach that includes the design of a user interface, integration of the IPFS API, implementation of an automatic hash-generation system, metadata storage in a database, and issuance of digital certificates. Testing results show that the system can automatically register digital works, generate unique and consistent file hashes, upload files to IPFS with an average upload time of less than two seconds, and provide global accessibility through a distributed network. In addition, the system is capable of validating the authenticity of a work by matching the hash and metadata listed in the digital certificate. Based on these findings, it can be concluded that the use of IPFS in digital IPR registration systems is effective in enhancing security, efficiency, and transparency, although further development is required in relation to integration with national legal frameworks and formal legal recognition.